2017
DOI: 10.1155/2017/2941432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Density and Harvest Interval on the Leaf Yield and Quality of Moringa (Moringa oleifera) under Diverse Agroecological Conditions of Northern South Africa

Abstract: Smallholder livestock farmers who depend on natural communal grazing lands are particularly vulnerable to climate change as well as to food insecurity and should be encouraged to grow drought-tolerant fodder crops. Moringa oleifera is a highly valued plant, due to its exceptionally high nutritional content. This study was conducted at two experimental sites in the Limpopo province of northern South Africa to evaluate for the first time the effect of plant density and cutting interval on biomass production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Even the same, our experiment displayed no difference among the height of the plants. Mabapa et al (2017) observed similar results as the authors assessed the effect of the density of planting in the productivity of the moringa. The authors described that the height of the plant was not affected by the different spacings and that the higher the cultivation density, the higher the production of dry matter per unity of surface occupied.…”
Section: Discussionsupporting
confidence: 78%
“…Even the same, our experiment displayed no difference among the height of the plants. Mabapa et al (2017) observed similar results as the authors assessed the effect of the density of planting in the productivity of the moringa. The authors described that the height of the plant was not affected by the different spacings and that the higher the cultivation density, the higher the production of dry matter per unity of surface occupied.…”
Section: Discussionsupporting
confidence: 78%
“…For selling the fresh leaves, they should be sold the same day since they lose moisture quickly after harvesting. Moringa can also be harvested at a height of 50 cm above ground level, which facilitates mechanical harvesting [5].…”
Section: Harvestingmentioning
confidence: 99%
“…Lower biomass was harvested at 481 and 281 DAP at Syferkuil and Ofcolaco compared to the other sampling dates. These periods coincided with the winter months where moringa dropped significant amounts of leaves, (Extracted from Mabapa, Ayisi [18]).…”
Section: Moringa Oleifera Trialmentioning
confidence: 83%
“…It is also known forits resistance to drought and diseases and also establishing well under harsh growing conditions where most trees cannot withstand [17]. Moringa oleifera can be cultivated in all five districts of the Limpopo Province under diverse climatic conditions [18]. In comparison with two dominant indigenous tree species, Mopane (Colophospermum mopane) and Marula (Sclerocarya birrea), moringa was reported to be superior in photosynthetic rate and stomatal conductance under drought conditions, indicating its potential for climate change mitigation [18].…”
Section: Introductionmentioning
confidence: 99%